Marriage empowerment through the Qur’ānic stories of husbands and wives - Jani, Nazrul Affandi; Samsudin, Sofiah; Mohmad, Nor Zatu Amni; , (Fakulti Pengajian Qur'an dan Sunnah, Universiti Sains Islam Malaysia (USIM), 2017)
Qur’ānic stories of husbands and wives give a glimpse of marital relationship as experienced by the selected couples whom Allāh has chosen to be recorded in the Qur’ān. There are twelve stories discussed in this paper as follows: (1) Ādam and his wife; (2) Nūḥ and his wife; (3) Ibrāhīm and his wife; (4) Lūṭ and his wife; (5) Egyptian Mayor and his wife; (6) Pharaoh and his wife; (7) Mūsā and his wife; (8) Zakariyyā and his wife; (9) Abū Lahab and his wife; (10) Muḥammad  and his wives; (11) Khawlah (al-Mujādilah) and her husband; (12) an ungrateful married couple. This qualitative study primarily uses historical methodology to portray and derive major lessons from the stories. The three key results of this research are: (1) there is a crucial need to expose Qur’ānic stories without deviating them with other unknown sources or details; (2) Qur’ānic stories of husbands and wives prove that marital life is an arena for jihād where married couples need to put their utmost efforts to strengthen their marriage; (3) virtues such as humility, patience and honesty are the vanguards for marriage, while vices such as arrogance, greed and infidelity are the destroyers of marriage.